PELATIHAN CORELDRAW UNTUK PENGEMBANGAN SOFT SKILL SISWA SMA IBRAHIMY 2 SUKOREJO - Hasna Ruhmaniatin; Jesika Maya Nur Islami; Zaehol Fatah (Jurnal Padamu Negeri, 2025)
CorelDRAW training for hing school students is a program aimed at improping graphic design competencies, with the aim of fostering creativity and digital skills in the cantext of contemporary tecnology. This training was conducted at ibrahimy sukorejo Hing School involving grade XI students as participants. CorelDRAW, recongnized as a leading vector designs, including logos, cover designs application, offers a variety of functions that facilitate the process of creating graphic designs, including logos, cover designs, and varius forms of visual media. This training initiative is designed to provide bacis knowledge about the use of CorelDRAW, starting from bacis principles such as tool use, color settings object management, to simple design development. The instructional metohodology includes presentations of theoretical materials complemented by hands-on practice sessions by students. Overall, this program makes a positive contribution to improving studts digital literacy and is the first step in forming a generation that is adeptive to technological devepments. The training assessment conducted on students reveald beneficial results in increasing motivatoin, thus encouraging enthusiasm for the field of graphic design. Through this training, students not only develop design-related skills but also develop the confidence needed to communicate ideas and messages effectively in a visual format